Development of smart system for agriculture - Kanna, Vitee (2022)
Agriculture is the practice of cultivating plants and livestock. To make the sustainable agriculture, this system is proposed. In this system Wi-Fi, HC12 (RF) and RTC Module DS3231 is used to control and monitor the irrigation system. This system provide easy to use for tum on and tum off solenoid valve. There are two types of on/off solenoid valve, first is regular tum on and off then it has timer on/ off for 5, 7 and 10 minutes. Auto irrigation also has been integrated to the system; system will tum on valve at 8am and 5pm for 10 minutes every day. There are 4 soil moisture sensor are used in this prototype. All the sensor can be monitor through the IOT Dashboard. The data from the sensor will be sending to the microcontroller then the data will be transfer to the IOT Dashboard and SD Card for offline data tracking. The IOT Dashboard can also analyze and view the collected data in the form of graphs, for better understanding. These data can improve the production.